Plasmonic coupling induced by growing processes of metal nanoparticles in wrinkled structures and driven by mechanical strain applied to a polidimethisiloxisilane template - Ugo, Cataldi; Thomas, Buergi (Photonics Letters of Poland, 2017)
We report the mechanical control of plasmonic coupling between gold nanoparticles (GNPs) coated onto a large area wrinkled surface of an elastomeric template. Self-assembly and bottom-up procedures, were used to fabricate the sample and to increase the size of GNPs by exploiting the reduction of HAuCl4 with hydroxylamine. The elastic properties of template, the increase of nanostructure size joined with the particular grating configuration of the surface have been exploited to trigger and handle the coupling processes between the nanoparticles. Full Text: PDF References G. Mie, "Beiträge zur Optik trüber Medien, speziell kolloidaler Metallösungen", Ann. Phys. 25, 377 (1908) CrossRef U. Kreibig and M. Vollmer, Optical properties of metal cluster, Berlin 1995 CrossRef S. A. Maier, Plasmonics: Fundamentals and Applications, Springer, New York, 2007 CrossRef L. A. Lane, X. Qian, and S. Nie, "SERS Nanoparticles in Medicine: From Label-Free Detection to Spectroscopic Tagging", Chem. Rev. 115, 10489-10529 (2015) CrossRef N. Pazos-Perez, W. Ni, A. Schweikart, R. A. Alvarez-Puebla, A. Fery and L. M. Liz-Marzan, "Highly uniform SERS substrates formed by wrinkle-confined drying of gold colloids", Chem. Sci. 1, 174-178P (2010) CrossRef M. Aioub and M. A. El-Sayed, "A Real-Time Surface Enhanced Raman Spectroscopy Study of Plasmonic Photothermal Cell Death Using Targeted Gold Nanoparticles", J. Am. Chem. Soc. 138, 1258-1264 (2016) CrossRef G. Baffou, and R. Quidant, "Thermo-plasmonics: using metallic nanostructures as nano-sources of heat", Laser Photonics Rev. 7, No. 2, 171-187 (2013) CrossRef G. Palermo, U. Cataldi, L. De Sio, T. Beurgi, N. Tabiryan, and C. Umeton, "Optical control of plasmonic heating effects using reversible photo-alignment of nematic liquid crystals", Applied Physics 109, 191906 (2016) CrossRef J. R. Dunklin, G. T. Forcherio, K. R. Berry, Jr., and D. K. Roper, "Gold Nanoparticle Polydimethylsiloxane Thin Films Enhance Thermoplasmonic Dissipation by Internal Reflection", J. Phys. Chem. 118, 7523-7531 (2014) CrossRef Y. Jin, "Engineering Plasmonic Gold Nanostructures and Metamaterials for Biosensing and Nanomedicine", Adv. Mater. 24, 5153-5165 (2012) CrossRef J. H. Lee, Q. Wu, and W. Park, "Metal nanocluster metamaterial fabricated by the colloidal self-assembly", Optics Letters 34, Issue 4, 443-445 (2009) CrossRef R. Pratibha, K. Park, I. I. Smalyukh, and W. Park, "Tunable optical metamaterial based on liquid crystal-gold nanosphere composite", Optics Express 17, Issue 22, 19459-19469 (2009) CrossRef J. Dintinger, S. Mühlig, C. Rockstuhl, and T. Scharf, "A bottom-up approach to fabricate optical metamaterials by self-assembled metallic nanoparticles", Optical Materials Express 2, Issue 3, 269-278 (2012) CrossRef T. Maurer, J. Marae-Djouda, U. Cataldi, A. G., Guillaume Montay, Y. Madi, B. Panicaud, D. Macias, P.-M. Adam, G. Léveque, T. Buergi, and R. Caputo, "The beginnings of plasmomechanics: towards plasmonic strain sensors", Front. Mater. Sci. 9(2) (2015) CrossRef J. N. Anker W. P. Hall, O. Lyandres, N. C. Shah, J. Zhao and R. P. Van Duyne, "Biosensing with plasmonic nanosensors", Nature Materials 7, 442 - 453 (2008) CrossRef M. E. Stewart, C. R. Anderton, L. B. Thompson, J. Maria, S. K. Gray, J. A. Rogers,and R. G. Nuzzo, "Nanostructured Plasmonic Sensors", Chem. Rev. 108, 494-521 (2008) CrossRef P. K. Jain , M. A. El-Sayed, "Plasmonic coupling in noble metal nanostructures", Chemical Physics Letters 487, 153-164 (2010) CrossRef P. K. Jain, W. Huang and M. A. El-Sayed, "On the Universal Scaling Behavior of the Distance Decay of Plasmon Coupling in Metal Nanoparticle Pairs: A Plasmon Ruler Equation", Nano Letters 7, 2080-2088 (2007) CrossRef U. Cataldi, R. Caputo, Y. Kurylyak, G. Klein, M. Chekini, C. Umeton and T. Buergi, "Growing gold nanoparticles on a flexible substrate to enable simple mechanical control of their plasmonic coupling", Journal of Materials Chemistry C 2(37), 7927-7933 (2014). CrossRef S. K. Ghosh and T. Pal, "Interparticle Coupling Effect on the Surface Plasmon Resonance of Gold Nanoparticles: From Theory to Applications", Chem. Rev. 107, 4797 (2007) CrossRef M. K. Kinnan and G. Chumanov, "Plasmon Coupling in Two-Dimensional Arrays of Silver Nanoparticles: II. Effect of the Particle Size and Interparticle Distance", J. Phys. Chem. C 114, 7496 (2010) CrossRef X. L. Zhu, S. S. Xiao, L. Shi, X. H. Liu, J. Zi, O. Hansen and N. A. Mortensen, "A stretch-tunable plasmonic structure with a polarization-dependent response", Opt. Express, 20, 5237 (2012) CrossRef K. H. Su, Q. H. Wei, X. Zhang, J. J. Mock, D. R. Smith and S. Schultz, "Interparticle Coupling Effects on Plasmon Resonances of Nanogold Particles", Nano Lett. 3, 1087 (2003) CrossRef Y. L. Chiang, C. W. Chen, C. H. Wang, C. Y. Hsieh, Y. T. Chen, H. Y. Shih and Y. F. Chen, "Mechanically tunable surface plasmon resonance based on gold nanoparticles and elastic membrane polydimethylsiloxane composite", Appl. Phys. Lett. 96, 041904 (2010) CrossRef N. Bowden, W. T. S. Huck, K. E. Paul, and G. M. Whitesides, "The controlled formation of ordered, sinusoidal structures by plasma oxidation of an elastomeric polymer", Appl. Phys. Lett. 75(17) (1999) CrossRef R, A. Lawton, C. R. Price, A. F. Runge, Walter J. Doherty III, S. Scott Saavedra , "Air plasma treatment of submicron thick PDMS polymer films: effect of oxidation time and storage conditions", Colloids and Surfaces A: Physicochem. Eng. Aspects 253, 213-215 (2005). CrossRef A Schweikart, N. Pazos-Perez, R. A. Alvarez-Puebla and A. Fery, "Controlling inter-nanoparticle coupling by wrinkle-assisted assembly", Soft Matter 7, 4093 (2011) CrossRef K. R. Brown, L. A. Lyon, A. P. Fox, B. D. Reiss and M. J. Natan, "Hydroxylamine Seeding of Colloidal Au Nanoparticles. 3. Controlled Formation of Conductive Au Films", Chem. Mater. 12, 314 (2000) CrossRef